1981
DOI: 10.5860/crl_42_05_470
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Noise in a College Library

Abstract: Ill Reducing Noise a College LibraryWhile it is known that high levels of noise (i.e., 90 + decibels [ dbs ]) can produce hearing loss, 4 even noise levels of less than 50 decibels can interfere with communication, the performance of complex tasks, relaxation, and sleep, and produce annoyance. 5 • 6 •7.8 Aircraft, railroad, traffic, and industry are major sources of noise and considerable effort has been directed toward reducing noise output from these sources. 9 However, "people noise" in classrooms, reside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…Evidence-based studies that explore the effectiveness of noise interventions are rare, due to the subjectivity of what is perceived as "noisy" and "quiet" and the difficulty in identifying metrics by which improvement can be measured. A small number of studies measured noise in decibels using sound-level meters; examples include the studies by Paul Luyben and his coauthors in 1981 9 and by Beth Hronek in 1997. 10 While decibel tests are an exact measure of actual noise, Luyben notes that perceived noise is a better measuring stick than actual noise because machines cannot measure disruptions such as "fierce whispering," which might not be loud but can be extremely annoying.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Evidence-based studies that explore the effectiveness of noise interventions are rare, due to the subjectivity of what is perceived as "noisy" and "quiet" and the difficulty in identifying metrics by which improvement can be measured. A small number of studies measured noise in decibels using sound-level meters; examples include the studies by Paul Luyben and his coauthors in 1981 9 and by Beth Hronek in 1997. 10 While decibel tests are an exact measure of actual noise, Luyben notes that perceived noise is a better measuring stick than actual noise because machines cannot measure disruptions such as "fierce whispering," which might not be loud but can be extremely annoying.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In another vein, research has demonstrated that the use of behavioral procedures reduced litter (Bacon-Prue, Blount, Pickering, & Drabman, 1980;Clark, Burgess, & Hendee, 1972;Hayes, Johnson, & Cone, 1975;Luyben, Lorini, & Chiaravalotti, 1984;O'Neil, Blanck, & Joyner, 1980) and decreased library (Luyben, Cohen, Conger, & Gration, 1981) and residence hall noise (Meyers, Artz, & Craighead, 1976).…”
Section: Community Involvement and The Environmentmentioning
confidence: 96%
“…Concern over noise in academic libraries is not new (e.g., Luyben et al, 1981). Yet, new types of collaborative, technology-enhanced learning spaces can often make libraries seem noisier (McCaffrey & Breen, 2016;Yelinek & Bressler, 2013).…”
Section: Commentarymentioning
confidence: 99%